Pengaruh Kualitas Pelayanan Pembuatan Surat Keterangan Catatan Kepolisian (SKCK) Terhadap Kepuasan Masyarakat dengan Menggunakan Metode Regresi Linier Berganda di Polrestabes Medan - Muhammad Ikhsan Harahap; Suliawati Suliawati; Siti Rahma Sibuea (Lembaga Pengkajian Dan Pengembangan Sumberdaya Pembangunan (lppsp), 2024)
The aim of this research is to determine the influence of the quality of SKCK manufacturing services on community satisfaction at POLRESTABES MEDAN. This research was conducted by analyzing the influence of the quality of SKCK manufacturing services on community satisfaction using the multiple linear regression method. From the results of the analysis carried out using the multiple linear regression method, the calculated t value for reliability (X1) was 10.33, while the significant level value was 0.00 and the t table was 2.019 with a significant level of 0.05 which can be interpreted as if t calculated > t table or probability > significant level or 10.33 > 2.019 and 0.00 < 0.05, then Ho is rejected and Ha is accepted which can mean that reliability has a big influence on people's satisfaction. And the empathy value (X2) t calculated was 8.537 while the significant level value was 0.00 while the t table was 2.019 with a significance level of 0.05 which can be interpreted that t calculated > t table or the probability > significant level or 8.537 > 2.019 and 0 .00 < 0.05 then Ho is rejected and Ha is accepted which means that reliability has a big influence on people's satisfaction.